Comparison of the Effects of Bromelain and Mefenamic Acid on Menstrual Bleeding in Students with Primary Dysmenorrhea: A Double-Blind Randomized Clinical Trial - Bibi Maryam Mirlashari; Zahra Abedian; Hasan Rakhshandeh; Habibollah Esmaily (Mashhad University of Medical Sciences, 2019)
Introduction: The rate of bleeding is associated with impaired synthesis of endometrial prostaglandins, especially PGE2. One of the most common causes of anemia in women is menstrual bleeding. Bromelain, an enzyme found in pineapple, has anti-inflammatory effects and reduces prostaglandin E2 in inflammatory regions. This study was performed with aim to compare the effects of Bromelain and Mefenamic acid on the amount of menstrual bleeding. Methods: A double-blind randomized clinical trial was conducted on 90 students with primary dysmenorrhea in dormitories of Velayat University of Iranshahr in 2017. The students were monitored for two cycles with Higham chart in terms of the rate of bleeding. Then, they were randomly assigned to two groups: Bromelain (n=32) and Mefenamic acid (n=34). The Higham chart was completed to measure menstrual bleeding in two cycles of control and two cycles of intervention. The subjects received 250mg capsules of Bromelain or 250mg capsules of Mefenamic acid, if needed, they received two interventional cycles every 6 hours during the first three days. Data was analyzed by SPSS software (version 22) and Mann-Whitney, Paired t-test and independent t-test. P <0.05 was considered significant. Results: The results of Paired t-test showed significant difference in the amount of bleeding after intervention in the Bromelain group (P = 0.036), but this difference was not significant in the Mefenamic acid group (P = 0.088). The difference between the mean of bleeding in two cycles of intervention compared to the two cycles of control was -6.79 ± 17.57 in the bromelain group and was -5.36 ± 17.57 in the Mefenamic acid group that showed no significant difference (P = 0.744). Conclusion: Consumption of Bromelain for reducing menstrual bleeding has no difference with Mefenamic acid in primary dysmenorrhea.